Особливості оцінки маркетингового потенціалу аграрних підприємств - Багорка, Марія Олександрівна; Bagorka, Mariya; Білоткач, Ігор Анатолійович; Bilotkach, Igor (Дніпровський державний аграрно-економічний університет, 2015)
Стверджується, що успіх діяльності будь-якого суб’єкта в ринкових умовах господарювання залежить, у першу чергу, від двох факторів: наявності ресурсів і вміння керувати ними з найвищою ефективністю. Підкреслено, що на сучасному етапі розвитку економіки особливої актуальності набувають питання пошуку оптимальних шляхів управління ресурсами підприємств з метою підвищення ефективності їх господарської діяльності. Зазначена проблема стосується такої складової підприємств аграрного сектору України, як маркетинговий потенціал. It becomes firmly established that marketing potential is one of major factors of providing of competitiveness of agrarian industry, which must be realized on internal and external markets by creation of the proper structures of management, systems of research of markets, development and introduction of marketing strategies. The special actuality is acquired by the questions of search of optimum ways of management of agrarian enterprises resources with the purpose of increase of efficiency them economic activity.Forming of marketing potential of agrarian enterprises has certain features. Marketing potential as difficult, multidimensional category needs specific going near its study. Thus, the special actuality for practice of management of enterprise is acquired by the problem of methodological subsoil of organization of processes in relation to research of parameters of marketing potential.The dynamic external environment of their functioning, which is characterized, influences on forming of marketing potential of agrarian enterprises, in particular, by the permanent changes of political situation in a country, socio-economic environment, tax and finansovo-kreditnoy policy, state of affairs of market.The timely estimation of marketing potential of enterprise will enable to discover and in time flexibly to react on changing of factors of external environment, compare possible directions of development of enterprise and define most perspective, set copulas between the state of enterprise and possible strategic directions of development, to segment the market of commodities and services, defining the most attractive for an enterprise segments, define the parameters of competitiveness of enterprise and market position in relation to a competitor, to define the alternative set of strategies for every economic unit with the purpose of acceptance of strategic administrative decisions in relation to a final choice and realization of strategies of development of enterprise.The well adjusted marketing, the task of which is an increase of the personal interest of workers in the effective use of resources and improvement of the state of realization of products, strengthening of material and technical base of enterprises, development of market infrastructure, organization of advertising, must become the main factor of increase of efficiency of production and realization of products of agrarian enterprise.
Features of forming and estimation of marketing potential of agrarian enterprises
Keywords: маркетинг; marketing; маркетинговий потенціал; marketing potential; аграрні підприємства; agrarian enterprises; методологія оцінки; methodology of estimation; оціночні показники; evaluation indexes; фактори середовища; factors of environment; служба маркетингу; service of marketing